Potensi Pengembangan Komunikasi Matematis Siswa Sekolah Dasar Melalui Pendekatan Realistic Mathematic Education - Ratna Purwati (Jurnal IAI Bunga Bangsa Cirebon, 2020)
Elementary school students' mathematical communication is still low, this can be seen from the inability of students to apply the knowledge they have acquired at school to solve problems in real life. The TIMSS report states that the ability of Indonesian students in mathematics communication is far below that of other countries. For example, for math problems involving mathematical communication skills, only 5% of Indonesian students were successful and far below countries such as Singapore, Korea and Taiwan, which reached more than 50%. This condition is probably influenced by the method of learning mathematics in elementary schools today, which mostly tends to emphasize the cultivation of procedural skills alone, is not contextual and does not equip students to be able to apply these concepts in solving math problems in life. Realistic Mathematic Education (RME) is an approach that has main characteristics, namely linking the mathematics content presented to the real life context, emphasizing the mathematical process, involving students' contributions in constructing conceptual understanding, interactive learning processes, and linking between concepts in mathematics. Students' mathematical communication that must be mastered by students involves oral and written communication. written communication skills are carried out with indicators, namely: the ability to express and illustrate mathematical ideas in the form of mathematical models, namely equations, notations, pictures and graphics, or vice versa. Based on its characteristics, RME has the potential to make a good contribution to communication development. Mathematical elementary school students. Abstrak Komunikasi matematis siswa SD masih rendah, hal ini tampak dari kekurangmampuan siswa dalam menerapkan pengetahuan yang diperolehnya di sekolah untuk menyelesaikan masalah dalam kehidupan nyata. Laporan TIMSS menyebutkan bahwa kemampuan siswa Indonesia dalam komunikasi matematika sangat jauh di bawah Negara-negara lain. Sebagai contoh, untuk permasalahan matematika yang menyangkut kemampuan komunikasi matematis, siswa Indonesia yang berhasil benar hanya 5% dan jauh di bawah Negara seperti Singapura, Korea, dan Taiwan yang mencapai lebih dari 50%. Kondisi tersebut kemungkinan dipengaruhi oleh metode pembelajaran matematika di sekolah dasar dewasa ini yang sebagian besar cenderung menekankan pada penanaman keterampilan prosedural semata, tidak kontekstual serta kurang membekali siswa untuk mampu menerapkan konsep tersebut dalam menyelesaikan masalah matematika dalam kehidupan. Realistic Mathematic Education (RME) merupakan pendekatan yang memiliki karakteristik utama yaitu mengaitkan konten matematika yang disampaikan dengan konteks kehidupan nyata, menekankan pada proses matematisasi, melibatkan kontribusi siswa dalam mengkonstruksi pemahaman konsep, proses pembelajaran interaktif, serta mengaitkan antar konsep dalam matematika. Komunikasi matematis siswa yang harus dikuasai siswa melibatkan komunikasi lisan dan tertulis. kemampuan komunikasi secara tertulis dilakukan dengan indikator-indikator yaitu: kemam puan menyatakan dan mengilustrasikan ide matematika ke dalam bentuk model matematika yaitu bentuk persamaan, notasi, gambar dan grafik, atau sebaliknya Berdasarkan karakteristik yang dimilikinya, RME sangat berpotensi memberikan kontribusi yang baik bagi pengembangan komunikasi matematis siswa sekolah dasar.